Injection moulding of long glass fibre reinforced polyamide 6-6: guidelines to improve flexural properties (eXPRESS Polymer Letters)
Based on a previous optimisation of set-up parameters for injection moulding of polyamide 6-6 (PA 6-6) reinforced with 40-wt% of 10 mm long glass fibre, the aim of this paper is to define suitable guidelines to further improve the mechanical performances of PA 6-6/glass long fibre thermoplastic (LFT) injection mouldings. Different solutions have been considered: screw and non-return valve design modification so as to adapt them to LFT processing, increase of the initial fibre content (up to 50 wt%) and length (up to 25 mm) in the LFT pellets. Using a LFT dedicated plasticating unit has allowed decreasing the fibre breakage amount by about 80% at the nozzle exit, however without improving the flexural properties. Increasing the initial fibre content has logically permitted to improve the flexural properties. Increasing the initial fibre length has not brought any improvement of the properties and has even amplified the structural heterogeneities and anisotropy of the parts. These trends have been explained on the basis of cavity pressure records highlighting significantly different rheological behaviours, and of resulting residual fibre lengths and through-the-thickness fibre orientation profiles modifications.